A 2D Ultrathin Nanopatterned Interlayer to Suppress Lithium Dendrite Growth in High‐Energy Lithium‐Metal Anodes (Adv. Mater. 34/2022). Issue 34 (25th August 2022) - Han, Kyu Hyo; Seok, Jae Young; Kim, In Ho; Woo, Kyoohee; Kim, Jang Hwan; Yang, Geon Gug; Choi, Hee Jae; Kwon, Sin; Jung, Edwin Ino; Kim, Sang Ouk
Abstract : Lithium‐Metal Anodes In article number 2203992, Jae Young Seok, Sang Ouk Kim, and co‐workers introduce an ultrathin multilayered protective layer under 1 μm, composed of lithiophilic Ag nanoparticle seeds, a 2D Li‐suppressing reduced graphene oxide (rGO) layer, and vertically porous block copolymer self‐assembled nanochannels for lithium‐metal anodes. The synergetic integration of each component enhances the mechanical robustness by stress relaxation, and homogenizes the Li‐ion flux at the same time. As a result, stabilized Li growth with a smooth interface and outstanding cycling stability can be achieved.